SOSIALISASI PEMBUATAN NIB KEPADA PELAKU UMKM DI DUSUN KALANGAN, CANDISARI, SECANG - Tri Nur Fadilah; Yeny Fitriyani; M Pudail (khidmatan, 2021)
This activity is intended to provide an understanding of the importance of applying for a business license and introducing a Business Identification Number (NIB) to apply for a business license online. Business legality is a standard that business actors must meet. Micro, Small and Medium Enterprises (MSME) are required to meet these requirements in order to compete in the free market era. This demand is a problem because many business actors do not have business legality. Therefore, community service activities are needed in the form of assistance, especially for craftsmen and MSME in order to develop their business in a better direction. The research method used is the PAR (Participatory Action Research) method. This study aims to provide knowledge and information on making NIB to business actors in order to develop their business. The results of this study were carried out by the community to understand and increase knowledge about making NIB which must be owned by every business actor. Then simplify business operations because they have obtained business legality.